The strange case of a patient affected by acromegaly with osteoporomalacia without hypogonadism - S. Caprio; P. Scagliusi; S. D'Amore; G. Minenna; M. D'Amore (PAGEPress Publications, 2011)
Acromegaly is a rare disease that, in the majority of cases, is due to the presence of a benign growth hormone (GH)- producing tumor of the pituitary. Growth hormone has profound effects on linear bone growth, bone metabolism, and bone mass. In acromegaly, the skeletal effects of chronic GH excess have been mainly addressed by evaluating bone mineral density (BMD). Most data were obtained in patients with active acromegaly, and apparently high or normal BMD was observed in the absence of hypogonadism. The Autors describe a case of patient affected by acromegaly without hypogonadism with serious osteoporosis and biological signs of osteomalacia.